Respuesta :

Answer: (3x-1)(4x+7)

For this case we make the product of the following expression:

[tex](3x-1) (2x ^ 2 + 4x + 3)[/tex]

To make the product we must apply distributive property that by definition establishes that:

[tex](a + b) (c + d) = ac + ad + bc + bd[/tex]

So:

[tex](3x-1) (2x ^ 2 + 4x + 3) =\\6x ^ 3 + 12x ^ 2 + 9x-2x ^ 2-4x-3 =[/tex]

We group similar terms:[tex]6x ^ 3 + (12x ^ 2-2x ^ 2) + (9x-4x) -3 =\\6x ^ 3 + 10x ^ 2 + 5x-3[/tex]

Answer:

[tex]6x ^ 3 + 10x ^ 2 + 5x-3[/tex]

ACCESS MORE